APPLICATION OF INQUIRY BASED LEARNING TO IMPROVE STUDENT CREATIVE THINKING ABILITY IN ELEMENTARY SCHOOL LEARNING SOCIAL STUDIES (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
One of the objectives of elementary school social studies learning is that students have the basic ability to think logically and critically, curiosity, inquiry, problem solving, and ability in social life. Therefore students are expected to develop the ability to think creatively by conducting inquiry learning to increase high curiosity. But in the application of learning, in general what is done by the teacher is only based on existing learning, there are students who are not active and less creative in the implementation of social studies learning. The purpose of this research is to explain the inquiry based learning to improve students' creative thinking skills in elementary school social studies learning. The research method used is descriptive qualitative research method. The subjects of this study were fourth grade students in one elementary school in Bandung City with a total of 32 students. After being analyzed, the results obtained from this study indicate that the inquiry based learning can improve students 'creative thinking skills in elementary school social studies learning, it is indicated by 1) students' curiosity becomes higher; 2) Students can have active discussion and questioning.